Maturity stages, variation within bunch and dormancy breaking treatments in relation to germination of oil palm (Elaeis guineensis Jacq.) D × P seeds - Ghazali, Mohd Norsazwan (2020)
Oil palm is mainly propagated through dura × pisifera hybrid (D × P) seeds. In natural environment, oil palm seeds require more than eight months of storage to achieve 25% germination due to seed dormancy. Currently, commercial seed producers adopt heat treatment to alleviate dormancy in D × P seeds with monthly germination ranging from 62.2% to 72.0% within four months after being harvested. Since the demand for oil palm is increasing, there is a need to increase the supply of pre-germinated D × P seeds. Therefore, improvement in percentage of germination, uniformity, and reduction in time to germination will benefit the industry tremendously. This thesis focuses on both the pre- and post-harvest factors in improving the germination of oil palm D × P seeds. In the first experiment, the effect of harvesting at three maturity stages (18, 20 and 22 weeks after pollination or WAP) and six seed positions within a bunch (Proximal-Base, Proximal-Apex, Middle-Base, Middle-Apex, Distal-Apex and Distal-Base) on seed qualities were evaluated in a split-plot design. Seeds harvested at 20 WAP had 80% black coloured seeds, 19% moisture content with highest germination of 85.1%, compared with 70.5% and 80.9% for 18 and 22 WAP, respectively. Increasing seed maturity from 18 to 20 WAP showed more seeds shifting from semi-white and white to black (up to 40% more). Seeds located at the base region of the spikelets were smaller in size and were predominantly white with no differences in germination capacity. In the second experiment, the morphological and physiological performance of oil palm D × P seeds varying in colour were evaluated. Four replicates of 10 and 100 seeds, laid out in Completely Randomised Design (CRD) were used for seed characterisation and germination test, respectively. Thirty pre-germinated D × P seeds from each replicate were then transferred to the nursery for morphological, physiological and growth assessment. Germination test showed that all the seed types indicated similar germination percentage (more than 78%) and speed (13- 15 days of mean germination time). The nursery assessment showed that seedlings from the black seeds have higher growth (biomass, total leaf area, stem diameter) for the first 3 months due to the relatively larger size of the seed. No differences in growth were observed from 6 until 12 months after sowing. Physiological evaluation including net photosynthesis (5.30 to 18.13 µmol CO2 m-2 s -1 ), chlorophyll contents (5.70 to 9.68 mg cm-2 ), stomatal conductance, transpiration rate as well as the intercellular CO2 concentration showed different seed colour produces physiologically similar normal seedlings. The third experiment was designed to elucidate the effect of eight dormancy breaking methods (operculum removal, 60 days storage, 60 days heat treatment, 120 days storage, 60 days storage + heat treatment, 180 days storage, 120 days storage + heat treatment and control) on seed germination based on physical, morphological, and physiological dormancy characteristics. The imbibition test indicated that less than 7% mass increment was recorded in all treatments after 240 hours of imbibition, while the embryo showed 10 to 20% increase in moisture after imbibition. Final germination of more than 82% was obtained for heat treated seeds, and seeds stored prior to heat treatments, along with less than 13 days of mean germination time. Morphological dormancy evaluation indicated that the embryo was fully developed at 20 WAP, but application of heat treatment was able to accelerate the growth after being imbibed. The physiological dormancy aspect was found to be associated with reduction in peroxidase (POD) and catalase (CAT) activities, along with increase in α-amylase production in the endosperm and embryo tissues. The heat and storage treatments cause up to 36 % reduction in POD and 13% in CAT activity levels, with 9% (endosperm) and 26% (embryo) increment of α-amylase. Based on these results, it can be suggested that oil palm seeds exhibit non-deep physiological dormancy (PD), with heat treatment of 40 °C as the most effective and practical dormancy-breaking method for commercial seed production. In the fourth experiment, the efficacy of fluctuating temperature in comparison to constant 30 °C condition on oil palm D × P seed germination was assessed. D × P seed samples from similar sources were placed in two locations (Banting and Renggam), as a nested design. Oil palm seeds recorded higher germination percentages and speed at fluctuating temperature (70 to 85%) in comparison with the constant 30 °C (55 to 65%). Results indicated that higher temperature amplitude at Renggam showed 15% higher germination than at Banting. In addition, it was found that higher α-amylase activity (209.0 to 223.7 units/ ul) was observed for seed that was germinated under fluctuating temperature condition. From this study, harvesting oil palm D × P fruit bunch at 20 WAP, and application of heat-treatment (40 ±2 °C) prior to germination at ambient fluctuating temperature condition are recommended to obtain 85% final germination within 17 days.